Diaquabis[N-(pyridin-4-yl)isonicotinamide-κN]bis(thiocyanato-κN)cobalt(II) - Uebler, Jacob W. (International Union of Crystallography, 2012)
In the title compound, [Co(NCS)(2)(C(11)H(9)N(3)O)(2)(H(2)O)(2)], the octahedrally coordinated Co(II) ion lies on a crystallographic inversion center and is bound by two isothiocyanate ligands, two aqua ligands and two N-(pyridin-4-yl)isonicotinamide (4-pina) ligands. The dihedral angle between the aromatic rings in the 4-pina ligand is 8.98 (11)°. In the crystal, the individual molecular units are aggregated in three dimensions by O—H⋯N, O—H⋯S and N—H⋯S hydrogen-bonding pathways.